2009
DOI: 10.1103/physrevb.79.165437
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiostudy of the diffusion and decomposition pathways ofSiHxspecies on Si(100)

Abstract: Diffusion and decomposition of SiH x species adsorbed on the clean Si͑100͒ surface are processes of relevance for the growth of crystalline silicon by plasma-enhanced chemical vapor deposition. In this work, we report an extensive search of diffusion and decomposition pathways for SiH 3 , SiH 2 , and SiH by means of combined ab initio metadynamics simulations and optimization of minimum-energy reactions paths. We find that on the clean surface SiH 3 undergoes stepwise decompositions into Si and H adatoms accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…These included studies on small solvated amino acids,79 polyoxometalates,80 beta‐ d ‐xylose condensation reactions,81 ester82 and formamide hydrolysis,83 and solvation84 and isomerization in water 85. The area of reaction at surfaces has also been explored to study chemical vapor deposition,86 heterogeneous reactions on carbon surfaces,87,88 and on anatase 89. Studies also included reactions in the solid state 90,91.…”
Section: Chemical Reactionsmentioning
confidence: 99%
“…These included studies on small solvated amino acids,79 polyoxometalates,80 beta‐ d ‐xylose condensation reactions,81 ester82 and formamide hydrolysis,83 and solvation84 and isomerization in water 85. The area of reaction at surfaces has also been explored to study chemical vapor deposition,86 heterogeneous reactions on carbon surfaces,87,88 and on anatase 89. Studies also included reactions in the solid state 90,91.…”
Section: Chemical Reactionsmentioning
confidence: 99%
“…The bottom three silicon layers are constrained at the bulk parameters, while the remaining layers are fully optimized. Previous studies have demonstrated that the supercell used in this work is sufficient for modeling the silicon surface. ,, It should be noted that we also performed test calculations for SiH 3 and Si 2 H 5 adsorption on six-, seven- and eight-layer Si(100) surfaces. The difference (less than 1.0 kcal/mol) of the adsorption energy can be neglected.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Kubo et al have used tight-binding quantum chemical molecular dynamics to simulate silicon crystal growth mechanisms for deposition of SiH 3 and SiH 2 radicals on the H-terminated Si(001) in a CVD process. , Maroudas et al reported several detailed studies on the hydrogen-induced crystallization mechanisms of amorphous silicon thin film via molecular dynamics (MD) simulations. Montalenti also showed hydrogen atoms can promote growth of ordered and epitaxial Si thin films in PECVD at low temperature on the H-terminated Si(001)-(2 × 1) by employing Car–Parrinello simulations and static density functional theory (DFT) calculations . In addition, DFT calculations have provided a way to obtain the electronic adsorption structures and the silicon-related reaction mechanisms accurately. In this work, we study the detailed mechanisms of the reactions of H atoms with adsorbed SiH x ( x = 1–3) and Si 2 H 5 species and predict the rate constants for the mentioned reactions by means of DFT calculations and transition-state theory (TST).…”
Section: Introductionmentioning
confidence: 99%
“…Its success and increasing popularity in the literature is due not only to the efficiency of the algorithm and the acceleration it offers in both classical MD and ab initio approaches but also to its versatility, as the choice of CVs that can be used is almost limitless. A wide array of CVs have been reported in the literature: structural order parameters to accelerate melting, clustering, and binding-type processes; , phase transitions have been induced using the simulation cell parameters as CVs; conformational changes of molecules have been accelerated using intramolecular bond angles or order parameters for CVs, including many studies of protein folding and other biological processes such as ion gating , and substrate binding; , and finally, simulations of chemical reactions have been accelerated using simple internuclear vectors, basic atomic coordinates, and coordination numbers as CVs. This versatility would clearly be a major advantage to the simulation of molecular machines, where the motions of different molecular components in a complicated system could each be represented by a separate CV in the multidimensional CV space of a single metadynamics simulation. The efficiency of the algorithm would then ensure that this complicated space was fully sampled.…”
Section: Introductionmentioning
confidence: 99%